RS PEMETAAN PROFIL DAN PERSEBARAN BANK SAMPAH DI PUSAT KOTA PADANG - Saftriko, Rakhes; Ahyuni, Ahyuni (DEPARTEMEN GEOGRAFI FIS UNP, 2026)
Abstract This study aims to determine the range of waste bank distribution services to the region, the range of waste bank distribution services to settlements in the center of Padang city, namely South Padang District, East Padang, West Padang, North Padang, and Nanggalo and the distribution pattern of waste banks seen from nearest neighbor analysis. This type of research is a quantitative description using a geographic information system (GIS). This research was conducted for 6 months in 2020, located in the city of Padang. The population in this study is a waste bank in the city of Padang with a total of 22 units while the sample is 8 units of a waste bank with total sampling. Technical analysis of data using profile data analysis techniques, distribution analysis (nearest neighbours), Network Analyst and service area analysis. The results show 1) analysis using the Service area Network method is obtained for the coverage of the most served area, namely Kec. Nanggalo where the area served is as wide as 1697.22Ha with a percentage of 92% and South Padang District with a small service area, which is 485.95 Ha with a percentage of 34%. So that the 6 points of the waste bank studied were able to serve the research area of ​​4611.47Ha with a percentage of 73%. 2) Settlements are served in 5 sub-districts, namely Nanggalo, West Padang, South Padang, East Padang and North Padang which have 6 Location Points for Garbage Banks. Kec. Nanggalo, the area that serves the most for serviced settlements, covers an area of ​​1169.66 Ha with a percentage of 99% served, Kec. East Padang served settlements covering an area of ​​430.17 with a percentage of 62% underserved is the least. So that from the 6 points the waste bank has served the research area covering an area of ​​3668.36 hectares with a percentage of 88%. 3) The service pattern of the 6 Waste Banks studied using the Nearest Neighbor analysis classified as 2022 spreads, this makes the waste Banks in the center of the city of Padang (Kec. Nanggalo, West Padang, South Padang, East Padang and North Padang) can be served ideally. Keywords: Distribution Pattern, Territory Coverage, Settlement Range, Waste Bank